Handbook on Cities and Complexity - Köseoğlu, Emine (Taylor & Francıs Ltd., 2022)
The book ‘Handbook on Cities and Complexity’ edited by Juval Portugali, in general, brings two basic words together: city and complexity. This is, indeed, a simple yet meaningfully strong attempt to propositionally phrase an engagement of cities and complexity both ontologically and epistemologically. Complexity, for Portugali, rooted in material science, is aimed to be considered as part of cognitive science when the city is included in the equation. The approach of complexity called a ‘new science of cities’ (p. 2) mostly bared on quantitative methods and modelling approaches. These terms and parameters sound quite solid. Seemingly, a new goal emerges and intersects with the one above: to fill the gap ‘between the quantitative and the hermeneutic’ (p. 2) approaches to the city. It appears to be a sign of accepting the city as an organic entity and also an analyzable system; however, as stressed in the book, the hermeneutic aspect has not been sufficiently addressed.